(untitled) (Agronomy Journal of Nepal, 2013)
An experiment was conducted at the Agronomy farm of the Institute of Agriculture and Animal Science (IAAS), Rampur, Nepal in 2008/09. The experiment was laid out in factorial design in spit plot arrangement consisting of date of sowing as main factor and wheat genotypes as sub factor. Wheat genotypes were sown in 22 November for normal sowing and 29 December for late sowing condition. These were assessed against Helminthosporium leaf blight and leaf rust severity in a naturally inoculated environment. Result showed that wheat genotypes differed significantly with respect to flag leaf area, flag leaf duration and plant height. Genotype BL-3064 showed the lower decline (624.9 to 615.1) in chlorophyll content whereas RR-21 showed highest decline (471.2 to 360.4) in chlorophyll content from normal to late sowing, possibly contributing to resistant to the disease. The AUDPC value revealed that genotypes BL-3625 and BL-3623 had increased level of resistance due to lower AUDPC value and higher flag leaf duration. The results of this study suggest that genotypes BL-3623, BL-3625, BL-3063 and BL-3064 could be the option in warm and humid regions of Terai condition so far as resistant to Helminthosporium leaf blight and leaf rust are concerned. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 109-116 DOI: http://dx.doi.org/10.3126/ajn.v3i0.9012